The Potential of Spent Bleaching Earth In Charcoal Briquettes as Energy Source - Tarigan, Enda Rasilta; Mirnandaulia, Meutia; Mustakim, Mustakim; Sitinjak, Anna Angela; Purba, Darry Christine Silowaty; Karo-Karo, Justaman Arifin; Silalahi, Meriahni; Fitri, Li Idi'il; Anwar, Dedy (Universitas Diponegoro, 2025)
Eco-friendly alternative fuels encourage the use of waste biomass as a material for making briquettes. This study aimed to develop briquettes from rice husk biomass and peat moss and add spent leaching earth (SBE). SBE is a hazardous and toxic waste increasingly piling up in landfills. The research method involved carbonizing rice husks and peat moss, mixing them with SBE, molding with a 200 kg/cm2 Hydraulic Press, and drying. The resulting briquettes had an average water content of 5.86% and an ash content of 2.18%, which meet the SNI No. 01/6235/2000 standard. Morphological analysis revealed that the briquettes were round but exhibited non-homogeneous aggregation. The highest calorific value was found in C4 briquettes of 5030.17 cal/gr. The composition of C4 was 40% rice husk charcoal (4.8 g), 45% peat (5.4 g), and 15% SBE (1.8 g), with SBE dried for seven days. The addition of peat increased the calorific value of the briquettes. Based on scanning electron microscopy (SEM)/ energy-dispersive X-ray (EDX) analysis, the carbon content in the C4 briquettes reached 72.2%. This study shows that the combination of rice husk charcoal, SBE, and peat provides a renewable energy source and contributes to the reduction of environmental waste, thereby promoting sustainability.